PENGGUNAAN METODE LATERAL THINKING UNTUK MENINGKATKAN KREATIVITAS MAHASISWA DALAM PENCIPTAAN KARYA DESAIN - Margana Margana (PAEDAGOGIA, 2010)
This research aims at: (1) improving teaching learning process quality ofAdvanced Visual Communication Design I by motivating students to be more active indigging creativity of creating Visual Communication Design Works (VCD), (2) improvingstudents’ creativity in creating innovative Visual Communication Design Works, (3)improving lecturer’s motivation and ability in conducting process and result evaluationin Advanced Visual teaching learning process. This research Communication Design Iconstitutes Classroom Action Research which is done at Art Department, FKIP UNS. Besubjects were the sixth sememester students. This research consists of 3 cycles in whicheach cycle consists of (1) planning, (2) implementing, (3) observing and interpreting, (4)analyzing and reflecting. The results of this research show that students are able to createVisual Communication Design Work and develop it to be creative work. The improvementof the shudents’ activity (75%) in teaching learning process can be seen from the morenumber of the students who convey their ideas in creating works interactively. Theimprovement of doing exploration (70%) can be seen from the more number of the studentsin finding techniques, media, and innovations in creating VCDW. The improvementof the motivation to out from the old convention of VCDW (75%) can be seen from themore number of ideas in creating works individually. The improvement of student’sconfidence (75%) can be seen from the more number of students’ works which are innovative,new, and fresh.